The impact of submesoscales on the stratification dynamics in the Southern Ocean - du Plessis, Marcel David (Department of Oceanography, 2019)
Submesoscale dynamics O(1-10 km, hours to days) are considered to strongly affect the stratification of the upper ocean. In the Southern Ocean, studies of submesoscale dynamics are biased to regions preconditioned for strong frontal activity and topographical influence. This dissertation considers the role of submesoscales on the evolution of mixed layer depth and upper ocean stratification in the open-ocean Subantarctic Ocean. First, we present autonomous ocean glider measurements from spring to late-summer to show that transient increases in stratification within the mixed layer during spring result in rapid mixed layer shoaling events. A realistically-forced simulation using a one-dimensional mixed layer model fails to explain these observed stratification events. We show that during this time, baroclinic mixed layer instabilities periodically induce a restratification flux of over 1000 W. m2, suggesting that the unexplained restratification is likely a result of submesoscale flows. Second, we study four separate years of seasonal-length (mid-winter to latesummer) glider experiments to define how submesoscale flows may induce interannual variations in the onset of spring/summer mixed layer restratification. Sustained temporal increases of stratification above the winter mixed layer, which defines the onset of seasonal restratification, can differ by up to 28 days between the four years studied. To explain this discrepancy, equivalent heat fluxes of baroclinic mixed layer instabilities (restratification) and Ekman buoyancy flux (restratification or mixing) are parameterized into a one-dimensional mixed layer model. Simulations including the parameterizations reveal a seasonal evolution of mixed layer stratification which is significantly more comparable to the glider observations than model simulations using heat and freshwater fluxes alone. Furthermore, the parameterization dramatically improves the sub-seasonal variability of mixed layer stratification, particularly during the onset of seasonal restratification when the mixed layer remains deep despite a positive surface heat flux. Following this, we characterize the full seasonal cycle of submesoscale flows using a realistically-forced 1/36 NEMO simulation of the Atlantic Southern Ocean. We show that deep winter mixed layers enhance the upper ocean available potential energy, which through the release of baroclinic mixed layer instabilities drive increased vertical buoyancy flux and potential to kinetic energy. These processes are associated with strong vertical velocities within the mixed layer characterized by large instantaneous upwelling and downwelling fluxes at the location of fronts. The insights from the glider observations propose that baroclinic mixed layer instabilities lead to increased near surface restratification in winter to spring, but are regulated by the synoptic-scale increases in Ekman buoyancy flux, which can keep the mixed layer deep for up to a month after surface warming. We propose the balance between restratification by baroclinic mixed layer instabilities and strong Ekman buoyancy flux driven by the passing of Southern Ocean storms is key in setting the large inter-annual variations of seasonal mixed layer restratification in the Subantarctic Ocean. Finally, we constrain the ability of gliders to represent regional submesoscale dynamics to provide context to current observations and inform future field work operations. Virtual gliders simulated within the 1/36 simulation show that horizontal buoyancy gradients in the Subantarctic are largely isotropic. We show that increasing the number of gliders sampling simultaneously over one month from one to a swarm of six results in improving the representation of the total distribution of horizontal buoyancy gradients across the Subantarctic from 10% to 42%. Similarly, by having a single glider sampling for six consecutive months, the distribution of horizontal buoyancy gradients observed increases to 47% of the total distribution. The insights presented in this dissertation enhance our understanding of submesoscale flows in the open-ocean Southern Ocean. These results are likely to have direct implications for physical and biological processes related to the ocean’s role on climate.